Assessing comorbid PTSD, depression, and anxiety in fibromyalgia patients: a retrospective observational study - Aneesh Rahangdale; Jeffrey Ferraro (BMC Psychiatry)
Abstract Background Fibromyalgia frequently coexists with psychiatric disorders, creating complex challenges in managing the health and quality of life for affected individuals. Existing literature points to significant overlap between fibromyalgia and conditions like posttraumatic stress disorder (PTSD), anxiety, and depression, but no large-scale analysis within a single American healthcare system has yet been conducted. Methods This retrospective observational study analyzed 1,516 fibromyalgia patients from HCA Healthcare facilities from January 1, 2022, to December 31, 2023, including only patients aged 18 and older with at least one psychiatric comorbidity. Chi-square tests examined associations between psychiatric outcomes (PTSD, depression, anxiety) and demographic factors such as age, sex, and race. Hospital length of stay (LOS) was analyzed among comorbidity groups using the Kruskal–Wallis test, with Bonferroni correction applied for pairwise comparisons. Results The sample had a mean age of 52.2 years, was predominantly female (95.98%) and white (77.51%). Anxiety (61.02%) and depression (39.75%) were highly prevalent, while PTSD was less common (8.64%). Significant age differences emerged. Younger patients had more PTSD than those 65 + years old. Those 30–39 years old had the highest PTSD prevalence. Conversely, the prevalence of depression increased with age, peaking in the 65 + years old group. Anxiety was more prevalent in the middle-aged patients, peaking in the 40–52 years old group. White patients and nonwhite patients did not have significant differences in PTSD, anxiety, or depression prevalence. Sex differences were significant for anxiety only (p = .028), showing higher rates among females (62% in females versus 48% in males). Mean LOS was 1.93 days, with significant differences across comorbidity groups (p = < .0001). Pairwise comparisons revealed that patients with only anxiety tended to have significantly shorter LOS than patients with only depression and with two psychiatric comorbidities (p < .001). Conclusions Psychiatric comorbidities are highly prevalent in hospitalized fibromyalgia patients and influence hospitalization outcomes. Anxiety, depression, and PTSD demonstrate unique relationships with age. The presence of multiple psychiatric comorbidities is associated with longer hospital stays, highlighting the need for integrated care approaches.